Exploratory study of the effect of one week of orally administered CNSA-001 (sepiapterin) on CNS levels of tetrahydrobiopterin, dihydrobiopterin and monoamine neurotransmitter metabolites in healthy volunteers - Smith, Neil; Longo, Nicola; Levert, Keith; Hyland, Keith; Blau, Nenad (Molecular genetics and metabolism reports, 2019)
Tetrahydrobiopterin (BH4) is a cofactor for the enzymes tyrosine hydroxylase and tryptophan hydroxylase, the rate-limiting enzymes in the production of the neurotransmitters, dopamine and serotonin, respectively, in the central nervous system (CNS). Administration of BH4 is used clinically within the management of persons with genetic BH4 deficiencies, but the BH4 molecule does not cross the blood-brain barrier sufficiently. CNSA-001 is a pharmaceutical preparation of sepiapterin, a natural precursor of BH4 that induced larger increases in plasma BH4 compared with administration of the same doses of BH4 itself in healthy volunteers in a randomized trial. Here, we report the effects of 7days of once-daily treatment with CNSA-001 60mg/kg (n=6) or placebo (n=2) on metabolites of the BH4 synthetic pathway and on biomarkers of the serotonin (5-hydroxyindoleacetic acid [5-HIAA]) and dopamine (homovanillic acid [HVA]) pathways in cerebrospinal fluid (CSF) in subjects from this trial. There were no notable changes in any metabolite in placebo-treated subjects. Administration of CNSA-001 increased mean BH4 from 18.1 (SD 3.0) to 35.1 (10.0) nmol/L, and of dihydrobiopterin (BH2) from 2.1 (0.3) to 7.9 (1.5) nmol/L. Overall, administration of CNSA-001 had little effect on mean levels (pre- vs. post-treatment) of 5-HIAA (76.1 [SD 29.8] vs. 70.1 [23.1] nmol/L) or HVA (177.2 [66.5] vs. 184.8 [35.3]) nmol/L. One subject with low 5-HIAA and HVA at baseline responded with approximately three-fold increases in CNS levels of these metabolites after CNSA-001 treatment, with post-treatment levels within the range of those seen in other subjects. Administration of CNSA-001 60mg/kg markedly increased levels of BH4 in the CNS of healthy volunteers, with apparently little overall effect in CNS levels of already normal key neurotransmitter metabolites.
Gesehen am 17.01.2019